1997
DOI: 10.1007/pl00005767
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the superior colliculus on the primate blink reflex

Abstract: In this study we used microstimulation to investigate the influence of the superior colliculus on the trigeminal blink reflex. We report that stimulation in the intermediate to deep layers of the tectum produced inhibition of reflex blinks at a latency of approximately 26 ms. We considered the hypothesis that the blink inhibition was mediated via the omnipause neurons (OPNs) of the eye movement control system in the brainstem. Our results show that the least effective sites for suppression were in the rostral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 38 publications
4
20
1
Order By: Relevance
“…Although the exact nature of how the BG influence the blink reflex remains uncertain, Basso (Basso and Evinger, 1996) postulated the sequential chain depicted in Figure 2, namely that increased SNr activity leads to increased inhibition of SC, leading to decreased excitation of the nucleus raphe magnus and decreased inhibition of trigeminal blink reflex circuits. This is consistent with evidence showing that SC stimulation suppresses the blink reflex (Gnadt et al, 1997) and that the SC is hypometabolic on FDG-PET in BEB (Emoto et al, 2010). Indeed, the pathway from SNr to the trigeminal nucleus has long been suspected to be involved in BEB (Hotson and Boman, 1991).…”
Section: Dynamic Circuit Hypothesis For the Pathogenesis Of Bebsupporting
confidence: 91%
“…Although the exact nature of how the BG influence the blink reflex remains uncertain, Basso (Basso and Evinger, 1996) postulated the sequential chain depicted in Figure 2, namely that increased SNr activity leads to increased inhibition of SC, leading to decreased excitation of the nucleus raphe magnus and decreased inhibition of trigeminal blink reflex circuits. This is consistent with evidence showing that SC stimulation suppresses the blink reflex (Gnadt et al, 1997) and that the SC is hypometabolic on FDG-PET in BEB (Emoto et al, 2010). Indeed, the pathway from SNr to the trigeminal nucleus has long been suspected to be involved in BEB (Hotson and Boman, 1991).…”
Section: Dynamic Circuit Hypothesis For the Pathogenesis Of Bebsupporting
confidence: 91%
“…Functionally, the rostral pole of layer 4 may subserve the suppression of saccades during visual fixation (Bü ttner-Ennever et al, 1999). Physiological recordings in the monkey SC showed that microstimulation of the deeper layers resulted in suppression of the blink reflex (Gnadt et al, 1997) or of blink-perturbed saccades (Goossens and van Opstal, 2000b).…”
Section: Trigeminocollicular Connectionsmentioning
confidence: 99%
“…It also receives afferent input from the trigeminal sensory nucleus (important for corneal and other trigeminally mediated blink reflexes) and dorsal midbrain (where reflexive blinking to light is mediated). Inhibitory microstimulation of the SC in primates has been shown to both suppress spontaneous blinking and increase sensitivity to blink reflexes (44, 45). …”
Section: Decreased Blinkingmentioning
confidence: 99%
“…In one study, for example, when the supraorbital nerve was stimulated twice over a period of 250 ms, the second R2 was 84% smaller in amplitude and 50% shorter in duration compared to the first R2 among healthy controls. By contrast, PD patients off therapy had only a 60% smaller and 10% shorter second R2 response (44). Dopaminergic therapy and STN DBS in both humans (61) and animals (62) restores blink reflex excitability to normal levels.…”
Section: Decreased Blinkingmentioning
confidence: 99%